Pelatihan Penyusunan Soal Bahasa Inggris Berbasis HOTS bagi Guru Bahasa Inggris SMP - Entika Fani Prastikawati; Wiyaka Wiyaka; Theresia Cicik Sophia Budiman (Jurnal Pengabdian Pada Masyarakat, 2021)
TRAINING ON COMPOSING HOTS-BASED ENGLISH QUESTIONS FOR ENGLISH TEACHERS OF JUNIOR HIGH SCHOOL. One of the changes in the newest curriculum applied in Indonesia, Curriculum 2013, is the standard of assessment. Assessment created by the teachers should be HOTS-based. İt should make students able to think critically and creatively. Knowing the importance of this and based on the survey result, community service was conducted. In the form of training, this activity aims at making English teachers of junior high school in Semarang be able to produce HOTS-based English questions. The training involved 30 English teachers of junior high school in Semarang who join MGMP. To know the result of the training, a questionnaire was distributed and a semi-structured interview was conducted. The result revealed that the training gave a positive effect on the teachers’ ability in producing HOTS-based English questions. They also had a good comprehension of the scoring system of HOTS. They know how to score students’ higher-order thinking skills. To sum up, the purpose of the training of composing HOTS-based English questions conducted was achieved.